PROBLEM PELAYANAN TERHADAP KELOMPOK PENGHAYAT KEPERCAYAAN DI PATI, JAWA TENGAH - Sulaiman Sulaiman (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2018)
The groups of penghayat kepercayaan have developed in many regions in Indonesia. However, the service discrimination still often occurs in the community. This study intended to find out the description of state service to the group of penghayat kepercayaan in obtaining their civil rights. The study used a qualitative approach. Data collection techniques used observation, in-depth interviews, and document review. The theory used was the theory of discrimination and service to see the social phenomena that exist in society. The findings showed that services to the Group of pengahayat kepercayaan, in general, were not optimal, especially on funeral services, population services, and religious education services. The cases of rejection on funerals for believers of pengahayat kepercayaan by the community, and the obligation to include religion on ID card even though they only adhered to the beliefs of penghayat kepercayaan, and did not accept the marriage of believers by the government. Likewise, the obligation of students to take religious subject is a problem for students who adhere to the beliefs. For believer groups of pengahayat kepercayaan who still embrace religious, they do not have a problem because they still recognize and practice their religious teachings. On the contrary, those who belong to the “pure” Believers are heavy because they consider it is a religion, such as Sapta Darma. Although in their daily lives, they still practice the procedures in the pengahayat kepercayaan, the policy of religious education services for a child who adhere the beliefs must follow the religious education determined by the school.